Molecular, morphological and survival analysis of 177 resected pancreatic ductal adenocarcinomas (PDACs): Identification of prognostic subtypes - Schlitter, Anna Melissa; Michalski, Christoph; Endris, Volker (Scientific reports, 2017)
Pancreatic ductal adenocarcinoma (PDAC) has generally a poor prognosis, but recent data suggest that there are molecular subtypes differing in clinical outcome. This study examines the association between histopathologic heterogeneity, genetic profile, and survival. Tumor histology from 177 resected PDAC patients with follow-up data was subclassified according to predominant growth pattern, and four key genes were analyzed. PDACs were classified as conventional (51%), combined with a predominant component (41%), variants and special carcinomas (8%). Patients with combined PDACs and a dominant cribriform component survived longer than patients with conventional or other combined PDACs. Genetic alterations in at least two out of four genes were found in 95% of the patients (KRAS 93%, TP53 79%, CDKN2A/p16 75%, SMAD4 37%). Patients with less than four mutations survived significantly longer (p = 0.04) than those with alterations in all four genes. Patients with either wildtype KRAS or CDKN2A/p16 lived significantly longer than those with alterations in these genes (p = 0.018 and p = 0.006, respectively). Our data suggest that the number of altered genes, the mutational status of KRAS and certain morphological subtypes correlate with the outcome of patients with PDAC. Future pathology reporting of PDAC should therefore include the KRAS status and a detailed morphological description.
Gesehen am 14.05.2018